Wheat and Grain Sorghum in Four-Year Rotations - A. Schlegel; J. D. Holman; C. Thompson (Kansas Agricultural Experiment Station Research Reports, 2018)
In recent years, cropping intensity has increased in dryland systems in western Kansas. The traditional wheat-fallow system is being replaced by wheat-summer crop-fallow rotations. Is more intensive cropping feasible with concurrent increases in no-till? Objectives of this research were to quantify soil water storage, crop water use, and crop productivity of 4-year and continuous cropping systems.
Keywords: four-year rotations; wheat and grain sorghum rotations; dryland rotation systems